The role of administrative leaders in some aspects of sports investment for Iraqi sports clubs (Journal of the College of Basic Education, 2022)
The study aimed to identify the role of administrative leaders in some aspects of sports investment for sports clubs. The researcher used the descriptive method in a survey method on a sample of administrative leaders in the Ministry of Youth and Sports, the Iraqi National Olympic Committee, the central federations and sports clubs, whose number is (191), and the scale (investment) was adopted. for sports clubs in Iraq) and conducting the scientific bases and transactions for it and applying it to the two exploratory samples and then the main one, and the results were processed automatically by the statistical bag system (SPSS)